Accountability and Transparency of Village Fund Budget Management - Warna, Warna; Hamzani, Umiaty; Rusmita, Sari (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The village is the smallest organization in the state government so that it cannot be separated from the government's attention so that the village is given the authority to manage several matters related to its own regional autonomy such as the management and planning of village funds, but in implementing these two things must be in accordance with the regulations of the Republic of Indonesia. The purpose of this study is to find out how the implementation of accountability and transparency in Batu Makjage village is. The approach used in this study is qualitative research. Data was collected using observation, interviews, and document studies. The types of data used are primary data and secondary data where primary data is obtained through interviews, observations and also documentation studies, namely several people who are considered sufficient as sources of information or data. Secondary data was obtained from several documents in the Batu Makjage village office including the Report Document on the realization of the implementation of the village revenue and expenditure budget for the final semester of the 2023 budget year. The results of the study show that the management of the village fund budget in this village has met the regulations and is in accordance with existing procedures, namely with accountability and transparency which is indicated by community participation and ease of accessing information related to planning and management of village funds.